Nurse's Experience in Treatment of COVID-19 Patients - Kitong, Berti Irwin; Arofiati, Fitri (JOSING: Journal of Nursing and Health, 2022)
This study aims to identify what nurses experience in handling COVID-19. The research uses a literature study with PI(E)O (patients, intervention/exposure, and outcome), and searches were carried out on the Proquest and PubMed databases. Google Scholar Research Results in nurses' feelings varied from stress and anxiety to mental depression about how to provide nursing care and services for COVID-19 patients. In conclusion, the experience of nurses in delivering services to Covid patients is divided into two, namely professionalism and psychology Keywords: Experience, Nurse, Care, COVID-19